Immunohistochemical Expression of p53 in Epithelial Ovarian Carcinoma and Its Correlation with Clinicopathological Parameters - Sharmin, Farzana; Noor-e-Ferdous, Noor-e-Ferdous; Akhter, Latifa; Nahar, Khairun; Islam, Towhidul; Ferdous, Jannatul (South Asian Journal of Cancer, 2025)
Mutation of p53 is often considered to be associated with high-grade epithelial ovarian cancer that carries a poor prognosis. The purpose of the study was to evaluate the pattern of immunohistochemical expression of p53 in epithelial ovarian carcinoma (EOC) and to find out its correlation with clinicopathological parameters of the disease.This observational, cross-sectional study was conducted at the Department of Gynecological Oncology, Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka, Bangladesh, from July 2022 to June 2023. A total of 50 women diagnosed with EOCs and scheduled for primary debulking surgery were selected for the study. A semiquantitative histochemical scoring method was employed for p53 nuclear staining, with over 1,000 tumor cells assessed across multiple high-power fields for percentage and intensity of staining. Positive and negative control slides were incorporated during staining procedures to ensure reliability. Statistical analyses included chi-square or Fisher's exact tests for categorical variables, Mann–Whitney tests for nonnormally distributed continuous data, and Spearman's correlation for relationships between various parameters.Of the total 50 study participants were included, 31 (62%) exhibited p53 mutations, while 19 (38%) showed no such mutations. The presence of p53 mutation was significantly associated with a family history of ovarian cancer (p = 0.001) and the histological subtypes (p = 0.046). Regarding histological subtypes, 39 (78%) cases were serous, 9 (18%) cases were mucinous, 1 (2%) case was seromucinous, and 1 (2%) case was of endometrioid variety. Preoperative median CA-125 levels were significantly higher in advanced-stage and high-grade serous ovarian carcinomas compared with early-stage and low-grade cases (p = 0.016 and p = 0.001, respectively). Although no significant association was found between p53 mutation status and serous carcinoma stage, mutation status was significantly associated with serous carcinoma grade (p = 0.042), with a moderate positive correlation (Spearman's correlation coefficient, ρ = 0.364).Our study highlights the significant association of p53 mutations with a family history and histological subtypes of EOC. Elevated preoperative CA-125 levels are associated with advanced-stage and high-grade serous carcinomas. Moreover, higher-grade serous ovarian carcinomas are significantly associated with the presence of p53 mutations, providing valuable insights into pathogenesis and potential treatment strategies.
Keywords: epithelial ovarian carcinoma (EOC); p53; clinicopathological parameters